Customer Engagement in the Digital Age: A Case Study of E-Commerce Platforms in Southeast Asia - Khoirul Syahri; Mohamad Sohir; Muti Mufaati (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Customer engagement is a crucial component of successful e-commerce platforms in the digital age, especially in rapidly growing regions like Southeast Asia. This research analyzes engagement strategies used by top e-commerce companies to retain customers and increase brand loyalty. Using a case study approach, data were collected from various platforms, focusing on user experience, loyalty programs, and digital marketing tactics. The findings reveal that personalized marketing and seamless mobile integration play significant roles in customer engagement. The paper concludes with recommendations for e-commerce businesses looking to improve customer interaction and loyalty in competitive digital landscapes.